تطور الفكر السياسي عند قدامى اليونانيين حتى أفلاطون (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هذا البحث هو محاولة للكشف عن الأسباب التي كمنت وراء تطور فكر سياسي عند اليونان،  بدأت في هذا البحث عرض مجموعة من النظريات والقوانين لأهم المشرعين  الحقوقيين في اليونان القديمة بدءاً من الملحمة الشهيرة "الإلياذة" وما تنطوي عليه من أفكار سياسية لعبت دوراً كبيراً عند مفكري اليونان وخاصة أفلاطون  بعد هذا ركزت على أهم شرائع صولون وأثرها على الفكر السياسي. ثم تناولت أهم المشكلات السياسية عند الفيثاغورثيين والسفسطائية اللذين كان لهم الدور البارز في صوغ نظريات فلسفية وسياسية وصولاً إلى فلسفة أفلاطون وما لها من انعطافات وآثار على الفكر الفلسفي بعامة والسياسي بخاصة . This paper is an attempt to review some of the reasons which underwrite, first, philosophic and, second, political thought in ancient Greece. I begin with a review of some of the theories and laws by some of the most prominent Greek legislators, starting with the with the all-too-famous Iliad and the underlying political ideas which played a significant role in the thought of Greece's thinkers, particularly Plato. Then, I move to shed light on some of Solon's most important laws and their effects on political thought. Further, I considered some of the basic political problems with Pythagoreans and Sophists who both had a significant  role in setting down philosophic and political theories, which later formed the foundations of Plato's philosophy, and the consequences and effects they had on philosophic thought generally and on political thought on particular.